Assistance to Boarding School Boarding School Administrators in English Language Development - Hidayatullah, Rizky; Pratiwi, Wiwied; Dwi Tobing, Dimas; Muhamad Agus Mushodiq (CV. BImbingan Belajar Assyfa, 2023)
The relationship between the world of education and Islamic boarding schools is the same thing and is interrelated. Many things are involved and included in it. The social sphere is something that cannot be separated from Islamic boarding schools. In this advanced era, several Islamic boarding schools carry out learning developed by many groups, namely learning English, which students must also master in the current era. The method used in this service is ABCD, namely the appreciative discovery process, asset development analysis, program strategy analysis, program narrative summary, program monitoring and evaluation techniques with dormitory management partners at Islamic boarding schools. The expected target of assisting Islamic boarding school boarding school administrators in developing English is to be able to create language agents for developing English in their respective Islamic boarding schools. The assistance, material and management will be provided in developing English in Islamic boarding schools. In this way, it is hoped that after assisting Islamic boarding school administrators who become English language agents, they can develop English in their respective Islamic boarding schools.